A case of amniotic fluid embolism and its sequelae during COVID-19 pandemic: a success story - Vishal, Anish Kumar; Bhasin, Dinesh; Prasad, Krishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Amniotic fluid embolism (AFE) is an unforeseeable, life-threatening complication of pregnancy with an extremely high mortality rate. This is a complex disorder classically characterized by the abrupt onset of hypoxia, hypotension and consumptive coagulopathy. We experienced a patient who underwent caesarean delivery because of sudden cardiovascular collapse. Intra op she had DIC and was hemodynamically unstable. Surgery was able to complete with inotropes and vasopressors. In subsequent post op period, she had sepsis with MODS. The diagnosis of amniotic fluid embolism was made after other differential diagnosis had been ruled out. The successful outcome in our case is attributable to early recognition with immediate delivery of the fetus, high-grade resuscitation, timely hysterectomy and aggressive treatment of coagulopathy by blood and blood-products, involvement of multidisciplinary team, constant supervision by nursing staff with positive approach. From a grim situation of near death, the final outcome was a successful story.